Relationship Between Smoking and Structural Damage, Autoimmune Antibodies, and Disability in Rheumatoid Arthritis Patients - Filiz SİVAS and Fatma Gül YURDAKUL and Ayşegül KILIÇARSLAN and Semra DURAN and Bedriye BAŞKAN and Hatice BODUR (Archives of Rheumatology, 2018)
Objectives: This study aims to investigate the relationship between smoking and structural damage, autoimmune antibodies, and disability in rheumatoid arthritis (RA) patients. Patients and methods: This cross-sectional study included 165 RA patients (36 males, 129 females; mean age 52.4±12.8 years; range 21 to 82 years). Disease duration, age at disease onset, smoking habits, rheumatoid factor (RF), and anti-cyclic citrullinated peptide levels were recorded. Morning stiffness, pain with visual analog scale, Health Assessment Questionnaire Scores And Disease Activity Score 28 were calculated. Patients’ standard hand radiographs were evaluated. Results: Patients were divided into three groups according to their smoking habits. Ninety-nine patients (60%) were never smokers, 45 patients (27.3%) were long-term smokers and 21 patients (12.7%) were new smokers. Three groups were compared for disease activity. Disease activity score 28 scores were 3.2±1.2, 3.2±1.3, and 3.2±1.4, respectively (p>0.05). The erosion score (2.6±5.8, 7.1±10.9, and 11.1±19.2, respectively) and joint space narrowing score (9.9±7.3, 18.6±14.9, and 17.3±12.3, respectively) according to modified Sharp method were significantly lower in never smokers group than other groups (p<0.05). RF titrations were 55.2±58.9, 60.5±63.1, and 84.9±71.5, respectively, and levels of long-term smokers group were significantly higher than the other groups (p<0.05). Joint space narrowing score was 16.2±11.9 and 6.4±10.4 in RF (+) and RF (-) patients, respectively (p<0.05). There was no significant relationship between anti-cyclic citrullinated peptide levels and others parameters. Conclusion: Although smoking is known as a poor prognostic factor in RA, there was no correlation between disease activity and smoking in our study. However, less radiographic damage was found in never smokers. Smoking does not appear to correlate with RA disease activity but it may be effective in the long-term joint damage.